2021
DOI: 10.2147/hiv.s303791
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Sociodemographic, Behavioral and Clinical Influences on Complete Antiretroviral Therapy Adherence Among HIV-Infected Adults Receiving Medical Care in Houston, Texas

Abstract: Introduction: Few studies have estimated complete antiretroviral therapy (ART) adherence following HIV infection since the advent of the new ART guidelines in 2012. This study determined the prevalence and influence of sociodemographic, behavioral, and clinical factors on complete ART adherence among people living with HIV (PLWH) receiving medical care in Houston/Harris County, Texas. Methods: Data from the Houston Medical Monitoring Project survey collected from 2009 to 2014 among 1073 participants were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
(100 reference statements)
0
2
1
Order By: Relevance
“…Previous studies have generally used the conventional approach of dichotomizing adherence or a maximum grouping into 3 levels of adherence. 32 In contrast to our findings, Storholm et al 33 analyzed electronically monitored adherence using the Medication Event Monitoring System in approximately 240 Black PWHIV in the United States at 3 points in time using GBTM. In that analysis, the model revealed 3 adherence trajectories, namely highly stable (40%), moderately low stable (35%), and low decreasing adherence (25%).…”
Section: Discussioncontrasting
confidence: 90%
“…Previous studies have generally used the conventional approach of dichotomizing adherence or a maximum grouping into 3 levels of adherence. 32 In contrast to our findings, Storholm et al 33 analyzed electronically monitored adherence using the Medication Event Monitoring System in approximately 240 Black PWHIV in the United States at 3 points in time using GBTM. In that analysis, the model revealed 3 adherence trajectories, namely highly stable (40%), moderately low stable (35%), and low decreasing adherence (25%).…”
Section: Discussioncontrasting
confidence: 90%
“…In the current analysis, GBTM provided a unique perspective on the evolving nature of WHIV adherence behavior, distinguishing ve categories of adherence across time. Prior studies generally utilized a traditional method of categorizing adherence into two or, at most, three categories, which miss changes in adherence over time [19]. In general, the ndings revealed that most predictors of membership in the continuously low and consistently moderate adherence trajectories (i.e., younger age, being non-Hispanic African American, higher education, any alcohol intake, being on ART for six or more years, and depression) have been described in the literature [20].…”
Section: Discussionmentioning
confidence: 99%
“…The other variable which signi cantly associated with unintended pregnancy was duration of ARV use, which using ARV for more than ve years was associated with more than twice [AOR:2.20, 95% ,CI = 1.28-3.79] higher to have an unintended pregnancy than women who were taking ARV for less than 5 years. It was consistent with the study done in Uganda,which women who have been taking ART drugs for more than 5 years were more likely to had unintended pregnancy as compared to those women who took for less than two years (18).This nding was also supported by a cross-sectional study carried out in America (32) and Malawi (28) which women who were living with HIV for more than ve years and women who were on ART for ≥ 2 years were more likely to experience unintended pregnancy respectively.This could be due to women using ARV for a long time may leads interaction of ARV and anti Tuberclosis medication with contraceptive method so there will be a failure of contraceptive (33).when women takes ARV for long time there will be poor adherence to contraceptive and there will burnout from using ARV drugs daily (34).women may also face problems with HIV-exposed infant because they need special care and attention than the general population.…”
Section: Discussionmentioning
confidence: 99%